Instagram Social Media as Peruri's Public Relations Strategy in Communicating with the Public - Anisa Diniati; Klara Tania Setyawan; Martha Tri Lestari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Social media provides almost unlimited connection opportunities. Organizational public relations place social media as a platform for carrying out public communication and strategic communication. Determining how to approach and forge relationship between the institution and the community is a strategic communication that the organization needs to put forward. Perum Peruri as the Money Printing Public Company of the Republic of Indonesia manages Instagram social media as part of the effort to communicate with the public. This study aims to see and describe how is Peruri's public relations strategy to utilize Instagram as a means of communication with the public. This research focuses on activities carried out in digital media; characteristics of digital media use; and strategic planning for communicating with the public. This research uses a qualitative approach and descriptive research type. The research took place for three months from October to December 2021. Data of the research was collected through an interview with Yahdi Lil Ihsan as the Secretariat, Protocol and Corporate Communication Bureau of Peruri, and observations through social media monitoring. The results of the study show that the Management of Instagram social media by Peruri aims to build an image as digital security with guaranteed product authenticity and safety.  Peruri's PR uses social media as its strategy for communicating with the public. The strategy comprises five stages including mapping the institution's image in the eyes of the public, conducting editorial planning, collecting data to create content, distributing content through Instagram social media, and evaluating (monitoring).